Advances in Biocatalytic Synthesis, Pharmacological Activities, Pharmaceutical Preparation and Metabolism of Ginsenoside Rh2 - Liu, Li; Wang, Huiyun; Chai, Xiaoyun; Meng, Qingguo; Jiang, Sheng; Zhao, Fenglan (Mini Reviews in Medicinal Chemistry, 2022)
Ginsenoside Rh2 (3β-O-Glc-protopanaxadiol), a trace but characteristic pharmacological component of red ginseng, exhibited versatile pharmacological activities, such as antitumor effects, improved cardiac function and fibrosis, anti-inflammatory effects, antibiosis and excellent medicinal potential. In recent years, increased research has been performed on the biocatalytic synthesis of ginsenoside Rh2. In this paper, advances in the biocatalytic synthesis, pharmacological activities, pharmaceutical preparation and metabolism of ginsenoside Rh2 are reviewed.
Keywords: pharmaceutical preparation